Post-communism an introduction - Holmes, Leslie 1948- (Polity Press, 1997)
Post-Communism: An Introduction examines the difficult issue of what is meant by "post-communism." Leslie Holmes presents a thematic and comparative discussion of the nature and history of post-communism, including discussion of the new political institutions, social movements and civil society, gender, the environment, nationalism and ethnic politics, and changing international allegiances. Throughout the work Holmes compares present circumstances with the pre-1989 situation in order to provide a fuller interpretation of post-communism. Comprehensive, comparative, and up-to-date, this accessible account of one of the major events of the 20th century will be essential reading for students of politics as well as the general reader.
Keywords: Geschichte 1985-1991; Postcommunisme; Kommunismus; Politik; Communism; Post-communism; Systemtransformation; Staatssozialismus; Zusammenbruch; Sowjetunion; Europe, Eastern -- Politics and government -- 1989-; Former Soviet republics -- Politics and government; Soviet Union -- Politics and government -- 1985-1991; Osteuropa